A longitudinal study of grapheme-color synesthesia in childhood: 6/7 years to 10/11 years - Simner, Julia; Bain, Angela E. (Frontiers in Human Neuroscience, 2013)
Grapheme-colour synaesthesia is a condition characterised by enduring and consistent associations between letter/digits and colours. This study is the continuation of longitudinal research begun by Simner, Harrold, Creed, Monro and Foulkes (2009) which aimed to explore the development of this condition in real time within a childhood population. In that earlier study we randomly sampled over 600 children and tested them aged 6/7 years and 7/8 years. We identified the child synaesthetes within that cohort and measured their development over 1 year, in comparison to a group of nonsynaesthetic children with both average and superior memories. We were able to show the beginnings of a developmental progression in which synaesthetic associations (e.g. A = red) mature over time from relatively chaotic pairings into a system of fixed consistent associations. In the current study we return to this same population three years later when participants are now 10/11 years. We used the same paired-association memory task to determine the synaesthetic status of our participants and to also establish synaesthetes’ inventories of grapheme-colour associations. We compared their inventories to those from age 6/7 year and 7/8 years to examine how synaesthesia matures over time. Together with earlier findings, our study shows that grapheme-colour synaesthesia emerges with a protracted lineal trajectory, with 34% of letters/digits fixed at age 6/7 years, 48% fixed at 7/8 years and 71% fixed at 10/11 years. We also show several cases where synaesthesia is not developing in the same time-frame as peers, either because it has died out at an older age, or because it was slower to develop than other cases. Our study paints the first picture of the emergence of synaesthesia in real-time over four years within a randomly sampled population of child synaesthetes.